Healing with Poisons Potent Medicines in Medieval China - Liu, Yan (University of Washington Press, 2021)
Open access edition: DOI 10.6069/9780295749013At first glance, medicine and poison might seem to be opposites. But in China's formative era of pharmacy (200-800 CE), poisons were strategically employed as healing agents to cure everything from abdominal pain to epidemic disease. Healing with Poisons explores the ways physicians, religious figures, court officials, and laypersons used toxic substances to both relieve acute illnesses and enhance life. It illustrates how the Chinese concept of du-a word carrying a core meaning of "potency"-led practitioners to devise a variety of methods to transform dangerous poisons into effective medicines.Recounting scandals and controversies involving poisons from the Era of Division to the Tang, historian Yan Liu considers how the concept of du was central to how the people of medieval China perceived both their bodies and the body politic. He also examines the wide range of toxic minerals, plants, and animal products used in classical Chinese pharmacy, including everything from the herb aconite to the popular recreational drug Five-Stone Powder. By recovering alternative modes of understanding wellness and the body's interaction with foreign substances, this study cautions against arbitrary classifications and exemplifies the importance of paying attention to the technical, political, and cultural conditions in which substances become truly meaningful.Healing with Poisons is freely available in an open access edition thanks to TOME (Toward an Open Monograph Ecosystem) and the generous support of the University of Buffalo.